On Zeros of One Class of Functions Analytic in a Half-Plane
We describe sequences of zeros of functions f ≢ 0 analytic in the half-plane \(C _ + = { z:Re z >0}\) and satisfying the condition \((τ_1 (0;1))(c_1 >0)(z C _ + ):|f(z)| c_1 (η^τ _1 (c_1 |z|)),\) where η: [0; +∞) → (0; +∞) is an increasing function such that the function ln η(r) is convex with respect to ln r on [1; +∞)., number=9, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Vynnyts’kyi, B. V. and Sharan, V.L., year=2003, month=Sep., pages=1254–1259